Pemberdayaan Masyarakat Melalui Pemanfaatan Sampah Anorganik Menjadi Produk Kerajinan yang Bernilai Ekonomis - Ambar Tri Ratnaningsih; David Setiawan; Latifa Siswati (Universitas Lancang Kuning, 2021)
Inorganic waste is a type of waste that is difficult to decompose naturally by microorganisms. Inorganic waste processing is carried out by collecting, disposing and transporting it to the final disposal site (TPA). There needs to be an effort to utilize inorganic waste, especially plastics, into useful products. People in Limbungan Village, Rumbai Pesisir District, Pekanbaru City already have a waste bank, but the benefits have not been felt by the community because inorganic waste is still being disposed of. There is a need for efforts to socialize and educate the public to process inorganic waste into handicraft products that have economic value. The method is carried out by educating the public about waste processing in general and demonstrating the use of plastic waste into handicraft products. After the counseling was carried out, the community had knowledge about waste management in general and skills in processing plastic waste into handicraft products such as bags, candy containers that were suitable for use and worthy of sale